2016
DOI: 10.1016/j.jrras.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some biological supplementation on productive performance, physiological and immunological response of layer chicks

Abstract: The present study was carried out to evaluate the effects of biological (Bacillus subtilis and Enterococcus faecium) supplementation on productive performance, physiological and immunological response of Hy-line layer chicks. Total of 300 one-day old of Hy-line layer chicks, were randomly divided into three groups. The first group was fed a basal diet and served as a control. While the second and third groups were fed the basal diet that supplemented with the probiotic mixture at the rate of 1 and 2 gm/kg of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 37 publications
9
23
0
Order By: Relevance
“…The obtained results were in accordance with the findings of Hussein, (2014) and Hatab et al (2016) who detected significant increase in serum glucose concentration in broilers fed on diets supplemented with probiotics as compared to the control. The increase in the serum glucose concentration may be due to a temperate amelioration gluconeogenesis and boosted lactose absorption (Das et al, 2005).…”
Section: Ne Ussupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results were in accordance with the findings of Hussein, (2014) and Hatab et al (2016) who detected significant increase in serum glucose concentration in broilers fed on diets supplemented with probiotics as compared to the control. The increase in the serum glucose concentration may be due to a temperate amelioration gluconeogenesis and boosted lactose absorption (Das et al, 2005).…”
Section: Ne Ussupporting
confidence: 92%
“…Many other positive impacts of probiotic supplementation in poultry have been well documented, including, accelerate development of normal microflora in the newly hatched chicks and protecting them against enteropathic disorders (Timmerman et al, 2005;Bansal et al, 2011), improving production performance, such as, feed intake, feed conversion efficiency and weight gain (Cruywagen et al, 1996;Cavit, 2003;Lesmeister et al, 2004;Awad et al, 2009;Alkhalf et al, 2010). Furthermore, the most important effect that it exerts body's resistance to infectious diseases (Santos and Ferket, 2006) and help lowering of chick mortality (Dhama et al, 2008;Hatab et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The mean of MCV and MCH was the highest in group H, therefore reduced count of RBC cannot be associated with iron deficiency. In our study probiotics decreased the level of ASAT; it coincided with other studies about the effect of probiotics on layer chicks (Gallus gallus domesticus L.) (Hatab, Elsayed, & Ibrahim, 2016). At the same time, there are other authors who have not observed this tendency (Liu et al, 2015).…”
Section: Effect Of Probiotics and Herbals On Health And Shedding Of Rsupporting
confidence: 92%
“…A growing body of scientific research shows that probiotics have beneficial effects on growth performance and intestinal microbiota balance in chickens (Chen, Gao, Zhu, Qin, & Qiu, ), piglets (Lan, Tran, & Kim, ) and aquaculture (Liu, Chiu, Wang, & Cheng, ; Niamphithak, Chareonwattanasak, & Doolgindachbaporn, ). Dietary BS exerts positive effects on production performance, improving the intestinal health and systemic immunity in poultry (Hatab, Elsayed, & Ibrahim, ; Lee, Lillehoj, Jang, & Lee, ). B. subtilis C‐3102 has been used as a direct‐fed microbial or probiotic product since 1986 to improve production performance in broilers worldwide (Silley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary BS exerts positive effects on production performance, improving the intestinal health and systemic immunity in poultry (Hatab, Elsayed, & Ibrahim, 2016;Lee, Lillehoj, Jang, & Lee, 2014). B. subtilis C-3102 has been used as a direct-fed microbial or probiotic product since 1986 to improve production performance in broilers worldwide (Silley, 2006).…”
Section: Introductionmentioning
confidence: 99%